A NOVEL SPECTROPHOTOMETRIC DETERMINATION OF METHYLDOPA THROUGH TERNARY COMPLEXATION PROCEDURE USING FE(III), MN(II), AND CO(II) WITH 2-AMINOPYRIDINE - KHALEEL BICHAN, MUSTAFA JAMAL; MUTEB ABDOON, FADAM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study is aimed to find a three simple, low cost, accurate, rapid, and sensitive spectrophotometric methods based on the formation of ternary complexes to assay methyldopa (MTD) in both pure and pharmaceutical dosage forms. Methods: The suggested complexation procedure is based on the formation of ternary complex among MTD, 2-aminopyridine (2-Amp), and different metal cations such as [Fe(III), Mn(II), and Co(II)] to form three complexes of Fe(III)-MTD-2-Amp (A), Mn(II)-MTD-2-Amp (B), and Co(II)-MTD-2-Amp (C) in an aqueous medium. Results: The obtained colored complexes are spectrophotometrically measured for the previously mentioned complexes at 572, 473, and 465 nm, respectively. Under optimum conditions, the complexes exhibited apparent, molar absorptivities of 1810.62, 2954.18, and 2596.8 l/mol/cm, Sandell’s sensitivity of 0.132, 0.08, and 0.092 μg/cm2, and Beer–Lambert’s law is obeyed over the ranges 4–40, 4–32, and 4–40 μg/ml for the three developed methods, respectively. Conclusion: The developed spectrophotometric methods showed excellent results in regard to accuracy and precision with recovery of 99.48±1.62%, 100.24±1.76%, and 100.72±1.65% of the complexes A, B, and C, respectively. The obtained results are compared statistically with a reported method with respect to t- and F-tests and the calculated results displayed no significant difference.